EPISTEMOLOGI USHUL FIQH - Badwi, Ahmad (DIKTUM: Jurnal Syariah dan Hukum, 2012)
Usul-Fiqh is the science of wealth treasury directly or indirectly, helped enrich our religious models. Implementation of Islamic Shariah will be hard if the science is not there, because-fiqh usul fiqh regarded as a guide is the answer for our lives. This science can answer some of the issues raised, it is that we can exploit, we should know the answer to what needs to be performed by this science. In Islam, all the texts of the Quran and Hadith al-zhanni shaped the meanings that emerge from the text was always formulated in a different conclusion (mukhtalaf FIH). For followers of the theory mushawwibah would say that all the disparate conclusions, which really is not one, in fact it could be all right. Similarly, if all the jurists show frameworks in line with the path-fiqh usul. While followers mukhaththiah would argue that all the conclusions that a lot of it, which is really just one, especially if there was some conclusions contradictory values. Approach to regional schools and schools of universal merefren basically on the corner of the development of usul fiqh itself. If ushuliyun it absurd to base its development on its own, meaning he developed a regional-fiqh usul